2019
DOI: 10.15537/smj.2019.2.23908
|View full text |Cite
|
Sign up to set email alerts
|

Methionyl-tRNA synthetase novel mutation causes pulmonary alveolar proteinosis

Abstract: The methionyl-tRNA synthetase (MARS) mutation is a very rare cause of congenital pulmonary alveolar proteinosis. We report a 6-month-old boy born with symmetrical intrauterine growth retardation presented with unexplained persistent tachypnea and hypoxemia associated with severe failure to thrive, anemia, hypoalbuminemia and hepatomegaly. Detailed pulmonary investigations including computed tomography chest scan, bronchoscopy and bronchoalveolar lavage revealed pulmonary alveolar proteinosis. Whole exome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our review of the literature identified 14 articles, 7 on LARS1 mutations and 7 on MARS1 mutations, such that including our 3 patients, 65 patients with LARS1 or MARS1 mutations (respectively 27 and 38) have so far been described in the literature. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Twenty-one of these patients (32.3%) patients died: 6/27 of the patients with LARS1 mutations (4 boys and 2 girls) and 15/38 of the patients with MARS1 mutations (11 boys and 4 girls). One of the patients with a LARS1 mutation underwent liver transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the literature identified 14 articles, 7 on LARS1 mutations and 7 on MARS1 mutations, such that including our 3 patients, 65 patients with LARS1 or MARS1 mutations (respectively 27 and 38) have so far been described in the literature. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Twenty-one of these patients (32.3%) patients died: 6/27 of the patients with LARS1 mutations (4 boys and 2 girls) and 15/38 of the patients with MARS1 mutations (11 boys and 4 girls). One of the patients with a LARS1 mutation underwent liver transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…MARS1 related PAP is a rare disease with an incidence of 1 in 10,000 new-borns in Réunion and nearby, and only a few case-reports have described this disease in other ethnic groups [3,[5][6][7][8][9][10], explaining the small sample size. P2 and P4 did not achieve complete remission of their liver involvement at the last follow-up with a persistent enlarged liver.…”
Section: Discussionmentioning
confidence: 97%
“…Enzymatic preparations purified from transfected E. coli have confirmed the significant impact of the mutations on the rate of the aminoacylation reaction (reduction of the k cat by 5 to 6-fold relative to wild type), especially for methionine affinity, as shown by a significant increase in the K m for methionine in mutants [4]. Patients of other ethnicities have been described, with other mutations but a very similar phenotype [3,[5][6][7][8][9][10]. As enzymatic activity can be restored by methionine supplementation in yeast, we aimed to treat successive patients with standardized methionine supplementation to assess safety and tolerance of such supplementation, and to compare the evolution of the treated patients to that of our historical cohort.…”
Section: Introductionmentioning
confidence: 83%
“…Finally, Alzaid et al (16) reported a 6-month-old boy with interstitial lung disease compatible with PAP, intermittent fever, axial hypotonia, hepatomegaly, hypoglycemia, hypothyroidism, anemia, thrombocytopenia. This patient also died of respiratory failure.…”
Section: Discussionmentioning
confidence: 99%